Dissecção endoscópica submucosa no tratamento da neoplasia superficial do esôfago: análise comparativa do método convencional versus técnica de tunelização - Tarso Magno Leite Ribeiro (2019)
Introduction: Endoscopic submucosal dissection (ESD) is the best approach for treatment of esophageal superficial neoplastic lesions, achieving a high rate of en bloc R0 ressection and low recurrence rate. Esophageal ESD requires a long learning curve and it is still restricted to tertiary centers. ESD strategy in the esophagus includes endoscopic submucosal tunnel dissection (ESD-TD) and the most traditional endoscopic submucosal dissection with circumferential incision (ESD-C). There are scarce reports in the West comparing clinical outcomes for existing ESD techniques. Objective: To compare the performance and clinical outcomes of ESD-TD and ESD-C. Methods: Single-center retrospective review of prospectively collected endoscopic data of a specialized ESD center in Brazil, investigating consecutive patients that underwent esophageal ESD for early squamous cells carcinoma and Barrett’s neoplasia, between October 2009 and December 2018. After placement of markings and submucosal injection, two different ESD strategies were assessed: ESD-TD - first set the anal incision then proceed to oral incision followed by submucosal dissection and tunnel making in the oral-anal direction; ESD-C – proceed a circumferential incision outside tumor borders followed by submucosal dissection. The following variables were assessed: demographic data, clinical-pathologic characteristics, procedure duration, en bloc resection rate, R0 resection rate, curative resection rate, local recurrence and adverse events. Results: A total of 65 procedures were carried out, 23 ESD-TD and 42 ESD-C, with a mean follow-up of 8 years and 2.75 years respectively (p=0.001). The demographic characteristics of patients and pathological data of the lesions were similar in both groups (p>0,05). There was no statistically significant difference in terms of clinical outcome among ESD-TD versus ESDC: en bloc resection rate (91.3% vs 100%, p=0.122), R0 resection rate (65.2% vs 78.6% p=0.241), curative resection rate (65.2% vs 73.8%, p=0.466), mean procedure time (118.7 min vs 102.4 min, p=0.351), local recurrence rate (8.7 vs 2.4, p=0.284), and procedure-related complications such as bleeding (0 vs 2.4%, p=0.53), perforation (4.3% vs 0%, p=0.610) and esophageal stricture (8.7% vs 9.5% p=0.310). There was no mortality related to the procedures. Conclusion: ESD-TD and ESD-C demonstrated to be equally safe, with low complication rate and zero mortality, presenting similar results in terms of clinical outcome for patients with superficial esophageal neoplastic lesions.